On Slavoj Žižek, Less Than Nothing: Hegel and the Shadow of Dialectical Materialism - Hamza, Agon (Stasis, 2016)
Book review: Slavoj Žižek, Less Than Nothing: Hegel and the Shadow of Dialectical Materialism